The Role of Islamic Religious Education Teachers in Increasing Students' Interest in Learning at Dinda Hafidzah Islamic School Middle School - Pulungan, Rizki Asroi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the teacher's role in increasing student interest in learning Islam at Dinda Hafidzah Junior High School. The data collection carried out in this study was by means of observation, interviews and documentation. The data analysis used in this research is using Miles and Huberman analysis techniques, the activities in the analysis include data reduction, data display and conclusion drawing and verification. While the technique of guaranteeing the validity of the data in this study uses triangulation techniques. The findings in this study: that Islamic religious education teachers have a role other than as educators and teachers, teachers also act as motivators and evaluators.